Preparation for Future Lockdowns: A Comparison of Student LMS Activity during and after COVID-19 - Lagmay, Ezekiel Adriel (Archīum Ateneo, 2023)
We use CausalImpact analysis to compare student online activity during the COVID-19 pandemic, when all classes were online, and post-pandemic, when classes were offered in a mix of modes. Student activity was operationalized as activity logs from the Canvas Learning Management System (LMS). When compared with student activity in pandemic fully online classes, we found that, contrary to our hypotheses, student activity in post-pandemic fully online classes decreased while activity in postpandemic fully onsite classes increased. We attribute the decrease in participation in fully online classes to factors such as Zoom fatigue and feelings of loneliness and prolonged isolation. The increase in student online activity in fully onsite classes might be explained by students' general preference for face-to-face interactions. They may have felt more connected to teachers and peers, leading to greater productivity overall. The discourse about the transition from online learning brought on by the pandemic is dominated by survey research. By examining student online activity in an LMS, this paper contributes an analysis of empirical data that supports the findings of prior studies about student perceptions of the online learning experience and their adjustments to the next normal.